(untitled) (Research, Society and Development, 2022)
Objective: To identify chronic complications associated with SARS-CoV-2 in mild to severe cases in health professionals at the Hospital Regional do Mato Grosso do Sul (HRMS). Methodology: Cross-sectional methodological design study by incidence, quantitative and descriptive. A survey form and the World Health Organization Disability Assessment Scale (WHODAS 2.0) were applied. Results: The study population was predominantly composed of women (75%) with a mean age of 38±9.7 years, working at the front line of the Regional Hospital of Mato Grosso do Sul, with clinical characteristics of arterial hypertension and obesity such as the main comorbidities reported. During infection, individuals reported fatigue and sore throat as the main respiratory symptoms. As for the symptoms of the Central Nervous System and Peripheral Nervous System, headache (38.63%) and anosmia (27.27%), respectively, were the most mentioned. In addition, they presented muscle pain related to the Skeletal Muscle System and sleep disorders, thus observing some neurofunctional and neuropsychological impairment associated with the infection. Through the assessment of WHODAS 2.0, the impact on the functionality of these individuals was observed. Conclusion: In this research, it was concluded that the domains of mobility, daily activities and the total score of disabilities assessed by WHODAS 2.0 had a significant negative correlation, showing deterioration in the functionality of the population under study. There is a need for more studies aimed at the young-adult population, reinforcing the importance of a biopsychosocial assessment.